RESIDENTIAL MOBILITY AND SOCIO-SPATIAL SORTING IN KADUNA METROPOLIS, NIGERIA - Olumide Akinwumi Oluwole (Indonesian Journal of Geography, 2013)
Residential mobility is a process which has significant effect on the urbanscape. The preferred directional biasof the mover households in Kaduna metropolis typifies the Schelling’s model of residential tipping whichultimately resulted in residential segregation. The level of the segregation was subjected to analysis by the useof multigroup analog, and was found to be 0.58. This index is moderately high. Also, residential mobility,amongst other factors led to the expansion of the metropolis, strengthen family ties and above all led to thesocio-spatial sorting of the residents. This study recommends continuous research in residential mobilitybecause it is very useful in the forecast of future landuse patterns which are critical to urban development.